(untitled) (قضايا سياسية, 2025)
This study aims to highlight the role of the advisory function in the rationalization of public policy in Algeria, while demonstrating the role of the National Economic, Social and Environmental Council in policy governance; Through his structure and functions provided by Algerian legislature,The study also aims to clarify the shortcomings and make some proposals through which the role and outputs of the advisory function in general and the role of the National Economic, Social and Environmental Council in particular as an adviser to the Government are developed